Terminal Plasmin Degradation Products Of Duck Fibrinogen - Krajewski, T; Nowak, P; Cierniewski, C S (Thrombosis and Haemostasis, 1981)
Previously we have found that duck or goose fibrinogen are built up of Aα, Bβ and γ chains like mammalian one. However, they are more sensitive to proteolytic action than pig fibrinogen and rapidly form the D-E complex. The aim of this report is to characterize terminal plasmic products of duck fibrinogen. The protein was digested in the presence of calcium ions with human plasminogen activated by streptokinase. Degradation products were firstly analysed by polyacrylamide gel electrophoresis, secondly, isolated by DEAE-cellulose chromatography and gel filtration on Sephadex G-100, thirdly, characterized in order to establish their peptide composition and amino acid content. Three fragments, namely fg-DH, fg-DM and fg-DL as well as single fragment E were identified among final degradation products. Under conditions used, fg-DH was the major form of fragment D with molecular weight of about 100,000. For fg-DM and fg-DL, fragments Mr 89,000 and Mr 80,000 have been found, respectively. All fragments differed in the length of gamma chain remnants which varied from Mr 42,000 to Mr 24,000. Only a single population of fg-E with Mr 43,000 was identified in plasmic degradation products. The constituent peptide subunits of that fragment were also characterized. Fg-D appeared to be a strong inhibitor of fibrin monomer polymerization both in homologous /duck fibrin monomers/ and heterologous /pig fibrin monomers/ systems.